1993
DOI: 10.1177/088610999300800306
|View full text |Cite
|
Sign up to set email alerts
|

Feminist Social Work Education in Mainstream and Nonmainstream Classrooms

Abstract: Women's courses continue to face questions about their contribution to the social work curriculum and their relevance for mainstream and nonmainstream students. The study described in this article compared the effects of feminist social work education in three classes of predominately white students with those in one class of native Canadian and immigrant students. In all the classes, the students' feminist identification increased, practice approaches changed, and self-esteem was enhanced. The effects in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Moreover, women issues courses in the social work curriculum increased the students’ feminist identification and enhanced their self-esteem. Further, a process has been specified by which the social work students incorporated gender awareness into their personal lives and professional stance (Pennell, Flaherty, Gravel, Milliken, & Neuman, 1993). While currently social work profession has an opportunity to assert its human rights focus (Healy, 2008), the results of the current study has demonstrated social work education can make important contributions to improve the equality in GPs.…”
Section: Discussion and Application To Social Work Practicementioning
confidence: 99%
“…Moreover, women issues courses in the social work curriculum increased the students’ feminist identification and enhanced their self-esteem. Further, a process has been specified by which the social work students incorporated gender awareness into their personal lives and professional stance (Pennell, Flaherty, Gravel, Milliken, & Neuman, 1993). While currently social work profession has an opportunity to assert its human rights focus (Healy, 2008), the results of the current study has demonstrated social work education can make important contributions to improve the equality in GPs.…”
Section: Discussion and Application To Social Work Practicementioning
confidence: 99%
“…Nevertheless, marginalized groups are pushing for an expansion of its knowledge base and methods and are urging a movement beyond conventional content and even prescriptions of cultural sensitivity to highlight alternative worldviews and practices and, particularly in the case of indigenous peoples, advancing their control over educational programs (see, e.g., Morrissette, McKenzie, & Morrissette, 1993;Pace & Smith, 1990;Pennell, Flaherty, Gravel, Milliken, & Neuman, 1993). In response, some social work educators (such as Leonard, 1994;Rossiter, 1993;Schriver, 1998) have urged the adoption of postmodern thinking to foster a climate for developing a critical pedagogy in social work education that attends to previously marginalized perspectives.…”
Section: Deconstructing/deconstructive Social Work Discoursesmentioning
confidence: 99%
“…Such an approach may be especially beneficial to instructors in schools of social work, where students are predominantly female. Teaching methods that are informed by feminist principles have been used for social work courses on research (Globerman & Chan, 2000), practice (Abram, Schmitz, Taylor, Tebb, & Bartlett, 2001;Bartlett & Tebb, 1995;Dore, 1994;Pennell, Flaherty, Gravel, Milliken, & Neuman, 1993), and policy (Pennell et al, 1993). This article describes the use of three feminist pedagogical strategies that involved computer technology in a social work course on oppression and diversity and evaluates the students' perceptions of the learning experience.…”
mentioning
confidence: 99%